BEAUTY AND MYSTERY OF GANDHARA ART - Rajput, Shahid Ahmad (Researcher: A Research Journal of Culture and Society, 2018)
This paper is a short history to establish the location, era and the main actors involved in the creation of a civilization what is generally known as Gandhara. It also includes a brief history of the Art and Architecture of Gandhara as the main feature and the beauty and mystery associated therein. Limitation of the length of paper will keep our discussion on three main centers as below. Necessary visual evidence is also included to justify the Beauty and the Mystery attached to the art of Gandhara for which this paper is initiated. Fact of the matter is that hundreds of books are written on Gandhara Civilization but this point “Beauty and Mystery of Gandhara” has hardly been addressed. This paper is therefore an attempt to fill the gap long felt by the author and last but not the least this paper is dedicated to the love and affection to the artwork of the monks who produced the Master Pieces of Gandhara, both in Stone and Stucco. The analysis is made according to the existing literature and author's own experience and interpretation. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 1-12